2000
DOI: 10.1136/gut.46.3.427
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alpha 2b combined with daily ketoprofen administration improves virological response in chronic hepatitis C: a prospective and randomised trial

Abstract: Background-Less than 15% of patients with chronic hepatitis C show a sustained virological response to interferon treatment. Aim-To evaluate the eYcacy and safety of diVerent doses of ketoprofen combined with interferon-2b in the treatment of chronic hepatitis C. Patients/Methods-Seventy compensated patients with chronic hepatitis C received interferon-2b 3 million units three times a week for six months. They were randomly assigned to: group 1 (n = 23), interferon2b alone; group 2 (n = 23), interferon-2b plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…[34][35][36][37] Some reports have indicated the failure of NSAIDs and interferon combination therapy in improving interferon-resistant chronic hepatitis C, 34,38 whereas other authors, using ketoprofen plus interferon, have reported an improved virological response in chronic hepatitis C patients. 35 Giambartolomei et al 39,40 reported that indomethacin potentiates the interferon-␣ signaling pathway by increasing signal transducer and activator of transcription 1 phosphorylation in vitro, improving cellular response. It must be noted that the aforementioned studies used NSAIDs with different biochemical activities and did not include comparable groups of HCV patients.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] Some reports have indicated the failure of NSAIDs and interferon combination therapy in improving interferon-resistant chronic hepatitis C, 34,38 whereas other authors, using ketoprofen plus interferon, have reported an improved virological response in chronic hepatitis C patients. 35 Giambartolomei et al 39,40 reported that indomethacin potentiates the interferon-␣ signaling pathway by increasing signal transducer and activator of transcription 1 phosphorylation in vitro, improving cellular response. It must be noted that the aforementioned studies used NSAIDs with different biochemical activities and did not include comparable groups of HCV patients.…”
Section: Discussionmentioning
confidence: 99%
“…If necessary, symptoms can generally be managed either by administration of agents such as acetaminophen and cyclo-oxygenase inhibitors prior to IFN-a or by dosereduction. There are no indications that administration of these agents adversely interfere with the antitumor activity of IFN-a 7,8 .…”
Section: Acute Toxicitymentioning
confidence: 99%
“…The ketoprofen group showed a significantly higher SVR rate (32.5%) than the control group (10%). Munoz et al . also showed that 6‐month interferon‐α‐2b therapy combined with ketoprofen was superior to interferon alone, for the treatment of naïve patients (SVR: 26% vs 5%).…”
Section: Discussionmentioning
confidence: 99%
“…Non‐steroidal anti‐inflammatory drugs (NSAIDs) are another class of drugs that may act as adjuvants for the treatment of chronic hepatitis C. In vitro studies have indicated that NSAIDs not only potentiate interferon signaling, via signal transducer and activator of transcription (STAT)1 phosphorylation, but also inhibited HCV RNA replication in Huh7 replicon cells . Two randomized trials showed that interferon monotherapy, combined with ketoprofen, increased the SVR rate, compared with interferon alone …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation